The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/s16122152
|View full text |Cite
|
Sign up to set email alerts
|

Secure Distributed Detection under Energy Constraint in IoT-Oriented Sensor Networks

Abstract: We study the secure distributed detection problems under energy constraint for IoT-oriented sensor networks. The conventional channel-aware encryption (CAE) is an efficient physical-layer secure distributed detection scheme in light of its energy efficiency, good scalability and robustness over diverse eavesdropping scenarios. However, in the CAE scheme, it remains an open problem of how to optimize the key thresholds for the estimated channel gain, which are used to determine the sensor’s reporting action. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Besides, RL has recently been regarded as a potential technique for solving MDPs efficiently (W. . In another study of Zhang and Sun (Zhang and Sun, 2016), they created a consensus transfer Q-learning algorithm with the aim of energy dispatch which shared Q-value matrices and used previous information to accelerate algorithm convergence. For dynamic economic dispatch, (Dai et al, 2020) suggested an RL method in which state-action-value function approximation was integrated with multiplier distributed optimization based on splitting.…”
Section: Reinforcement Learning and Metaheuristic Algorithmsmentioning
confidence: 99%
“…Besides, RL has recently been regarded as a potential technique for solving MDPs efficiently (W. . In another study of Zhang and Sun (Zhang and Sun, 2016), they created a consensus transfer Q-learning algorithm with the aim of energy dispatch which shared Q-value matrices and used previous information to accelerate algorithm convergence. For dynamic economic dispatch, (Dai et al, 2020) suggested an RL method in which state-action-value function approximation was integrated with multiplier distributed optimization based on splitting.…”
Section: Reinforcement Learning and Metaheuristic Algorithmsmentioning
confidence: 99%
“…How to optimize these comparison thresholds is not discussed by the authors in [ 27 ]. In [ 28 ], the optimal thresholds were derived to further improve the performance. When relays are used in IoT networks with passive eavesdroppers with locations, a randomize-and-forward relay scheme has been proposed in [ 29 ].…”
Section: Related Workmentioning
confidence: 99%
“…In particular, the authors introduce an interesting security model with a self-adaptive schema that enables a system to automatically meet the environmental parameters, hence offering the corresponding protections. A study on secure distributed detection problems under energy constraint for IoT-oriented sensor networks is proposed in [ 23 ]. In particular, authors focus on how to optimize the key thresholds for estimating the channel gain in Channel-Aware Encryption (CAE).…”
Section: Related Workmentioning
confidence: 99%